2011
DOI: 10.1680/muen.2011.164.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Implementing bike-sharing systems

Abstract: The growing popularity of bike-sharing systems around the world has motivated recent attention to models and algorithms for the effective operation of these systems. Most of this literature focuses on their daily operation for managing asymmetric demand. In this work, we consider the more strategic question of how to (re-)allocate dock-capacity in such systems. We develop mathematical formulations for variations of this problem (service performance over the course of one day, long-run-average performance) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Authors concluded that costs and emissions can be saved by the combined usage of cargo bikes and vans instead of vans alone. Dell'Olio [23] estimated the potential demand of a public bicycle system and the optimization of pick-up and drop-off point's locations. Lin and Yang (2010) also proposed a methodology for estimating the location and number of docking stations needed for a given system.…”
Section: State Of the Artmentioning
confidence: 99%
“…Authors concluded that costs and emissions can be saved by the combined usage of cargo bikes and vans instead of vans alone. Dell'Olio [23] estimated the potential demand of a public bicycle system and the optimization of pick-up and drop-off point's locations. Lin and Yang (2010) also proposed a methodology for estimating the location and number of docking stations needed for a given system.…”
Section: State Of the Artmentioning
confidence: 99%
“…Since most major cities have planned or considered implementation of bike sharing systems, and existing systems are often expanded, several studies present models dedicated to strategic design. Dell'Olio et al (2011) develop a comprehensive methodology for implementation, from estimating potential demand to optimizing locations. Martinez et al (2012) and Prem Kumar and Bierlaire (2012) present MIP models for the location problem.…”
Section: Related Workmentioning
confidence: 99%
“…The design decisions are made with consideration for both total cost and service levels. Dell'Olio et al (2011) [7] present a complete methodology for the design and implementing of bicycle sharing systems based on demand estimates considering the stations and the fares. Vogel et al (2011) [38] develop a methodology for strategic and operational planning using data mining.…”
Section: A Review Of the Literaturementioning
confidence: 99%